Down-Regulation of Telomerase Activity in Malignant Lymphomas by Radiation and Chemotherapeutic Agents - Lin, Zhaosheng (American Society for Investigative Pathology, 2001)
The effects of radiation and cytotoxic agents on telomerase activity in lymphoma cells were analyzed by a polymerase chain reaction-based telomeric repeat amplification protocol coupled with an enzyme-linked immunosorbent assay, reverse transcriptase-polymerase chain reaction for the expression of the catalytic subunit of telomerase (hTERT), and by Western blot analysis in three lymphoma cell lines (Jurkat, Raji, CEM-6). Telomeric repeat amplification protocol-enzyme-linked immunosorbent assay demonstrated high basal levels of telomerase activity in all cell lines compared to normal and activated peripheral blood lymphocytes. A significant decrease in telomerase activity was observed in all cell lines after exposure to vincristine for 24 hours. The decrease in telomerase activity paralleled the decrease in cell viability in Jurkat and CEM-6 cells but not in Raji cells. Radiation exposure inhibited the telomerase activity of Jurkat and CEM-6 cells whereas Raji cells were unaffected. Cell cycle analysis demonstrated a significant G(2)/M arrest by cisplatin, VP-16, and vincristine. In contrast to the decline in telomerase activity, the level of hTERT RNA and protein increased. Furthermore, the induction of hTERT was preceded by increased expression of the cyclin-dependent kinase inhibitor, p27/Kip1 protein, and p53. These results indicate that telomerase activity is down-regulated by anti-neoplastic agents in lymphoma cells, however expression of hTERT may not be correlated with telomerase activity. We also show that p27/Kip1 may be involved in the G(2)/M growth arrest induced by anti-neoplastic agents.